Csk differentially regulates Src64 during distinct morphological events in Drosophila germ cells. - O'Reilly, A.M.; Ballew, A.C.; Miyazawa, B.; Stocker, H.; Hafen, E.; Simon, M.A. (Development, 2006)
The Src family protein tyrosine kinases (SFKs) are crucial regulators of cellular morphology. In Drosophila, Src64 controls complex morphological events that occur during oogenesis. Recent studies have identified key Src64-dependent mechanisms that regulate actin cytoskeletal dynamics during the growth of actin-rich ring canals, which act as intercellular bridges between germ cells. By contrast, the molecular mechanisms that regulate Src64 activity levels and potential roles for Src64 in additional morphological events in the ovary have not been defined. In this report, we demonstrate that regulation of Src64 by Drosophila C-terminal-Src Kinase (Csk) contributes to the packaging of germline cysts by overlying somatic follicle cells during egg chamber formation. These results uncover novel roles for both Csk and Src64 in a dynamic event that involves adhesion, communication between cell types and control of cell motility. Strikingly, Src64 and Csk function in the germline to control packaging, not in migrating follicle cells, suggesting novel functions for this signaling cassette in regulating dynamic adhesion. In contrast to the role played by Csk in the regulation of Src64 activity during packaging, Csk is dispensable for ring canal growth control, indicating that distinct mechanisms control Src64 activity during different morphological events.